Characteristics of Nanocrystallite-CdS Produced by Low-Cost Electrochemical Technique for Thin Film Photovoltaic Application: The Influence of Deposition Voltage - Obi Kingsley Echendu; Francis Birhanu Dejene; Imyhamy Mudiy Dharmadasa; Francis Chukwuemeka Eze (International Journal of Photoenergy)
Electrochemical deposition and characterization of nanocrystallite-CdS thin films for thin film solar cell application are reported. The two-electrode system used provides a relatively simple and cost-effective approach for large-scale deposition of semiconductors for solar cell and other optoelectronic device application. Five CdS thin films were deposited for 45 minutes each at different cathodic deposition voltages in order to study their properties. X-ray diffraction study reveals that the as-deposited films contain mixed phases of hexagonal and cubic CdS crystallites with large amounts of internal strain and dislocation density. Postdeposition annealing results in phase transformation which leaves the films with only the hexagonal crystal phase and reduced strain and dislocation density while increasing the crystallite sizes from 21.0–42.0 nm to 31.2–63.0 nm. Photoelectrochemical cell study shows that all the CdS films have n-type electrical conductivity. Optical characterization reveals that all samples show similar transmittance and absorbance responses with the transmittance slightly increasing towards higher growth voltages. All the annealed films show energy bandgap of 2.42 eV. Scanning electron microscopy and energy dispersive X-ray analyses show that grains on the surface of the films tend to get cemented together after annealing with prior CdCl2 treatment while all the films are S-rich.